CREATION OF TERMINOLOGICAL DICTIONARIES IN UZBEK AND KARAKALPAK LANGUAGES: PROBLEMS AND SOLUTIONS - Okhunjan Abdullaev (International Journal of Literature and Language Studies, 2026)
Annotation. This article is devoted to the issues of creating a new generation of terminological dictionaries related to fields in the Uzbek and Karakalpak languages. It is well known that the vocabulary and terminological system of languages are constantly enriched, and this process is inextricably linked to the development of science and technology, the expansion of socio-economic and cultural ties, and the development of other fields. Currently, in these fields, along with the terms included in the explanatory dictionaries of the Uzbek and Karakalpak languages, the meanings of which have been explained, there are a number of terms that have not yet been included in dictionaries but are used in communication. This, in turn, leads to a misunderstanding of the meanings of terms or their use without understanding at all. The easiest way to eliminate such a problem is to create explanatory dictionaries of terms related to the fields. We know that such dictionaries cover a large area in terms of volume. Therefore, there is a need for new generation dictionaries that combine the capabilities of modern information technologies and the currently popular artificial intelligence. This article discusses the necessity of such dictionaries and how terms are interpreted in two languages.